Using Technology to Improve Capacity Management at a Pediatric Hospital. (November 2020) - Foreman, Cynthia; Stephens, Kimberly; Swanson-Biearman, Brenda; Acree, Cynthia; Whiteman, Kimberly
Abstract : Bed flow decisions should be based on current information about capacity. The purpose of this project was to develop a real-time, enterprise-wide, capacity management dashboard. The dashboard successfully used information from the electronic medical record to create a comprehensive standardized data source, which was used to drive patient flow decisions optimizing bed space, allocating resources and maintaining safety.